The Southern Lady and the Northern Publishers: A Tumultuous Relationship. - Censer, Jane Turner (Journal of Southern History, 2019)
The article discusses the experiences of white southern female authors attempting to become published authors and their dealings with northern publishers during the late 19th century, particularly focusing on the experience of author Amélie Rives, in addition to her correspondence with author Thomas Nelson Page.